Multiscale modeling for bioresources and bioproducts. (April 2018) - Barnabé, M.; Blanc, N.; Chabin, T.; Delenne, J.-Y.; Duri, A.; Frank, X.; Hugouvieux, V.; Lutton, E.; Mabille, F.; Nezamabadi, S.; Perrot, N.; Radjai, F.; et al.
Abstract: Designing and processing complex matter and materials are key objectives of bioresource and bioproduct research. Modeling approaches targeting such systems have to account for their two main sources of complexity: their intrinsic multi-scale nature; and the variability and heterogeneity inherent to all living systems. Here we provide insight into methods developed at the Food & Bioproduct Engineering division (CEPIA) of the French National Institute of Agricultural Research (INRA). This brief survey focuses on innovative research lines that tackle complexity by mobilizing different approaches with complementary objectives. On one hand cognitive approaches aim to uncover the basic mechanisms and laws underlying the emerging collective properties and macroscopic behavior of soft-matter and granular systems, using numerical and experimental methods borrowed from physics and mechanics. The corresponding case studies are dedicated to the structuring and phase behavior of biopolymers, powders and granular materials, and to the evolution of these structures caused by external constraints. On the other hand machine learning approaches can deal with process optimizations and outcome predictions by extracting useful information and correlations from huge datasets built from experiments at different length scales and in heterogeneous conditions. These predictive methods are illustrated in the context of cheese ripening, grape maturity prediction and bacterial production. Highlights: Modeling approaches help understand properties of bioresources and bioproducts. Modeling can account for multi-scale phenomena, heterogeneity and variability. Physical modeling gives access to collective properties of soft-matter and granular systems. Interactive machine-learning approaches can help model complex food systems.